Decomposition of between and within-country (regional) differences in the labour market attainment of young adults - Carla Hornberg; Jan Paul Heisig; Heike Solga (INVEST Research Flagship Centre, University of Turku, 2024)
This report provides insights into inequalities in school-to-work transitions (hereafter STWT) by exploring the role of contextual and individual factors in shaping the experiences of young people. We examine differences between 27 European countries and, for 14 of them, also within countries across major socio-economic (NUTS 1) regions, using EU-SILC data from 2021 (during the COVID‑19 pandemic) and comparing it with 2018 to assess whether the COVID-19 pandemic had an impact. We map success and inequalities in the labour market outcomes of young adults using six indicators – labour market integration with risks of unemployment and NEET, and occupational attainment, and as related outcomes, income in/security with young adults' disposable income and poverty risks, and young adults' life satisfaction. We explore whether labour market integration and related outcomes are associated with other life domains, i.e. whether there are spillovers in both directions between labour market entry and other transitions to adulthood, such as economic independence (leaving parental home) or family formation (entry into marriage/cohabitation and parenthood). We also examine the interaction with young adults' health, a factor that is often missing in STWT research.
Keywords: 370; school-to-work transitions; COVID 19; labour market outcomes; young adults; mapineq